Standardizing terminology for minimally invasive pancreatic resection. Issue 3 (March 2017) - Montagnini, Andre L.; Røsok, Bård I.; Asbun, Horacio J.; Barkun, Jeffrey; Besselink, Marc G.; Boggi, Ugo; Conlon, Kevin C.P.; Fingerhut, Abe; Han, Ho-Seong; Hansen, Paul D.; Hogg, Melissa E.; Kendrick, Michael L.; et al.
Abstract: Background: There is a growing body of literature pertaining to minimally invasive pancreatic resection (MIPR). Heterogeneity in MIPR terminology, leads to confusion and inconsistency. The Organizing Committee of the State of the Art Conference on MIPR collaborated to standardize MIPR terminology. Methods: After formal literature review for "minimally invasive pancreatic surgery" term, key terminology elements were identified. A questionnaire was created assessing the type of resection, the approach, completion, and conversion. Delphi process was used to identify the level of agreement among the experts. Results: A systematic terminology template was developed based on combining theapproach andresection taking into account thecompletion . For a solitary approach the term should combine "approach + resection" ( e.g . "laparoscopic pancreatoduodenectomy); for combined approaches the term must combine "first approach + resection" with "second approach + reconstruction" ( e.g. "laparoscopic central pancreatectomy" with "open pancreaticojejunostomy") and where conversion has resulted the recommended term is "first approach" + "converted to" + "second approach" + "resection" ( e.g. "robot-assisted" "converted to open" "pancreatoduodenectomy") Conclusions: The guidelines presented are geared towards standardizing terminology for MIPR, establishing a basis for comparative analyses and registries and allow incorporating future surgical and technological advances in MIPR.